National Policy in a Global Economy - Budge, I. author. aut Link
VI, 113 p.
Keywords: This study offers an analysis of the UK's current economic policy options and a plan for improving life for ordinary citizens via a sensible and realistic understanding of governments' limited ability to manage economic performance. It provides a manifesto which political parties could immediately adopt to make life better for all.